Improving the Ex Vitro Adaptation Technology for Vaccinium Angustifolium and Vaccinium Corymbosum on the Field - Sergey S. Makarov; Anton I. Chudetsky; Irina B. Kuznetsova; Elena I. Kulikova; Andrey N. Kulchitsky; Natalia R. Sungurova (Техника и технология пищевых производств)
Russian food market is striving to substitute imported blueberry products and planting material. This research featured the effect of various substrates and growth stimulators on the survival rate and morphometric parameters of blueberry ex vitro in the climate of Moscow. The study involved six cultivars of Vaccinium corymbosum L. (Bluecrop, Bluegold, Denise Blue, Duke, Kaz Pliszka, Patriot) and six cultivars of V. angustifolium Ait. (Northblue, Northcountry, Lakomka, Nerl, Neya, Pomorochka). The ex vitro experiment included various compositions of peat substrates and growth-stimulating preparations (Zircon, Epin-Extra) at the stage of adaptation to non-sterile conditions. Mulching with litter and sawdust of coniferous trees and treatment with Zircon and Epin-Extra were used in the field conditions. The highest survival rate (82–89%) of V. angustifolium in non-sterile conditions ex vitro belonged to the Russian cultivars treated with Epin-Extra 0.5 mL/L on mixes of peat and vermiculite (3:1) and peat and zeolite (3:1). The largest number of shoots (4.5–5.0 pcs.) was registered on peat and perlite (3:1). The highest survival rate on high-moor peat was 100% for annual V. angustifolium and 75–90% for V. corymbosum. The largest number of shoots (5.0–8.7 pcs.) was obtained from the samples treated sawdust and pine-and-spruce waste. The survival rate was 95–100% for perennial V. angustifolium and 84–90% for V. corymbosum. The maximal total shoot growth was observed after Epin-Extra 0.5 mL/L. The optimal substrates and growth regulators could be used to improve blueberry propagation for industrial cultivation in the soil and climate of Russia’s Central Non-Chernozem Zone. Epin-Extra made it possible to increase the number of shoots during ex vitro adaptation and on high-moor peat. Sawdust and pine litter had a positive effect on shoot formation for annual blueberry plants in the field.